Exploring creative thinking skills in PISA: an ecological perspective on high-performing countries - Sevinc Gelmez Burakgazi; Sevinc Gelmez Burakgazi; Michael J. Reiss (Frontiers in Psychology)
IntroductionCreative thinking is a growing focus in educational reforms worldwide. Extensive research explores its development, measurement, various conceptions, and pedagogical approaches like creative teaching and teaching for creativity. A significant development in this area was the inclusion of creative thinking as an innovation domain in the 2022 Programme for International Student Assessment (PISA). The PISA 2022 assessment sought to evaluate the ability of 15-year-old students across 64 jurisdictions to generate, evaluate, and improve original and diverse ideas.MethodsThis paper examines the key findings of the PISA 2022 creative thinking results from three high-performing jurisdictions in different parts of the world: Singapore, Canada, and Finland. We use Bronfenbrenner’s ecological perspective to understand the interplay of various systemic influences on students’ creative thinking abilities within these educational contexts.ResultsOur analysis, informed by Bronfenbrenner’s framework, highlights how different ecological systems may contribute to their observed outcomes.DiscussionWhile acknowledging the complexities and potential pitfalls of directly transferring educational policies between countries, this paper discusses the implications of these findings for school education. We suggest that researchers, policymakers, and educators can gain valuable insights by examining the policies, contexts, and practices of these high-performing nations through an ecological lens, fostering a deeper understanding of how to nurture creative thinking in diverse educational settings.